Thought vs. memory in education - Kersey, Ralph Teeter (My University, 1904)
Introduction: It is only by the power of thought that one is able to infer that what is true in a given case is likely to be true in a similar case, and thus profit by experience. It is thought that enables us to reap the benefits of our successes and failures. It is thought that makes possible all the advancement of invention, science and art, that brings natural resources in the service of man, and contrives all the developing agents of civilization.
Citation: Kersey, Ralph Teeter. Thought vs. memory in education. Senior thesis, Kansas State Agricultural College, 1904.
Morse Department of Special Collections
Keywords: Education; Curriculums in Education; Society Well-Being; Theses